2018
DOI: 10.1002/ange.201713221
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Interconversion between Boroxine Cages Based on Pyridine Ligation

Abstract: Dynamic interconversion between large covalent organic cages was achieved simply by heating or acid/base treatment. A mixture of the boroxine cages 12‐mer and 15‐mer was cleanly converted into a pyridine adduct of the 9‐mer boroxine cage upon treatment with pyridine, and the geometry of N‐coordinated boron atoms changed from trigonal to tetrahedral. The reverse reaction was achieved by heating or acid treatment. In this process, the larger boroxine cages 12‐mer and 15‐mer were found to be entropically favored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Dynamic covalent chemistry [8] exploits the reversibility of bond‐breaking and formation for a variety of applications from the self‐assembly of supramolecular architectures [9] to bioconjugation, [10] and the development of self‐healing polymers, [11] malleable thermoset materials [12] and gels [10a,13] . Dynamic covalent bonds include disulfides, [9e,f,14] C−O bonds [8d] (e. g. esters, [15] acetals [16] and orthoesters [9a,b] ), Si−O bonds, [17] C=N bonds (e. g. hydrazones, [14c,18] imines [9g,i,m,19] ) and B−O bonds (e. g. boronate esters, [9h,j,k,10a,14c,20] boroxines [5b,9l,12a,21] ). Combining imine and boronate ester bonds, iminoboronates are self‐assembled from an amine, 2‐formylphenylboronic acid and a diol using dynamic covalent chemistry [8c,22] .…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic covalent chemistry [8] exploits the reversibility of bond‐breaking and formation for a variety of applications from the self‐assembly of supramolecular architectures [9] to bioconjugation, [10] and the development of self‐healing polymers, [11] malleable thermoset materials [12] and gels [10a,13] . Dynamic covalent bonds include disulfides, [9e,f,14] C−O bonds [8d] (e. g. esters, [15] acetals [16] and orthoesters [9a,b] ), Si−O bonds, [17] C=N bonds (e. g. hydrazones, [14c,18] imines [9g,i,m,19] ) and B−O bonds (e. g. boronate esters, [9h,j,k,10a,14c,20] boroxines [5b,9l,12a,21] ). Combining imine and boronate ester bonds, iminoboronates are self‐assembled from an amine, 2‐formylphenylboronic acid and a diol using dynamic covalent chemistry [8c,22] .…”
Section: Introductionmentioning
confidence: 99%
“… 10 Recent studies have been conducted to understand the structural interconversion mechanisms of boroxine cages containing pyridine that will enable the optimization of several properties such as porosity and size‐selective molecular recognition. 11 , 12 Besides, in previous gas‐phase studies, different substituted boroxines were irradiated with electrons above the ionization potential, 13 , 14 and one DEA study was also performed on triphenylboroxine. 15 In these studies, triphenylboroxine was demonstrated to be stable towards fragmentation upon electron interaction, 15 and the stability of boroxines is affected by the substituent on the boron atom.…”
Section: Introductionmentioning
confidence: 99%